2020
DOI: 10.3389/fphys.2020.00474
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Innervation Coupling With Vascularity: The Role of Electro-Acupuncture in Follicular Maturation in a Rat Model of Polycystic Ovary Syndrome

Abstract: Tong et al. Electro-Acupuncture Induces Ovarian Neurovasculature Coupling preovulatory follicles and corpora lutea compared with those in the right non-sectioned ovary. In conclusion, ovarian innervation likely played an important role in folliculogenesis, and EA might restore PCOS pathophysiology by regulating ovarian innervation, at least partially mediated through the SON.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…A total of 31 studies were included [ 13 , 14 , 19 46 ]. Thirteen studies were published in English, and 18 were published in Chinese.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 31 studies were included [ 13 , 14 , 19 46 ]. Thirteen studies were published in English, and 18 were published in Chinese.…”
Section: Resultsmentioning
confidence: 99%
“…It has been newly demonstrated that ovarian innervation likely plays an important role in folliculogenesis, and EA might restore PCOS pathophysiology by regulating ovarian innervation, at least partially mediated through the superior ovarian nerve. The effect of EA is based on the integrity of the nervous system [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent 3D study of innervation in postnatal and adult mouse ovaries using CUBIC-clearing Tong et al (2020) showed that each follicle is innervated by a single neural fiber; furthermore, peripheral nerve branching around follicles increases at later stages of folliculogenesis ( Figure 1D ). They further showed that PMSG-induced follicular growth contributed to a visible increase in TH-positive neuronal fibers in the ovary within 48-h. Tracing the long and circuitous routes of nerve fibers could not be accomplished through traditional histology, but is ripe for 3D techniques.…”
Section: Clearing Techniques and Quantitative Approaches Used For Assessment Of Ovaries In 3dmentioning
confidence: 92%
“…EA treatment partially rescued the PCOS-like phenotype by increasing total vascular area and volume, particularly in mature follicles, suggesting that elevated blood flow allows mature follicles to receive signals required for ovulation. The role of innervation in PCOS pathology and its possible treatment via EA therapy were also studied in rat ovaries using CUBIC clearing and 3D analysis ( Tong et al, 2020 ). EA treatment reversed the increased innervation in the ovarian stroma and the diminished neuronal network around individual follicles in PCOS-like ovaries.…”
Section: D Analysis Of the Ovary In Different Speciesmentioning
confidence: 99%
“…Also, experiments on PCOS animal models showed that electrical acupuncture (EA) ameliorated insulin resistance and mitochondrial dysfunction by promoting autophagy [11]. EA regulates ovarian innervations to increase the numbers of preovulatory follicles in PCOS-like rats [12].…”
Section: Introductionmentioning
confidence: 99%